Danau Toba sebagai Ruang Moderasi Beragama dan Teologi Pariwisata dalam Perspektif Hermeneutika Biblika - Limbong, Sukanto; Suprabowo, Gunawan Yuli Agung; Panjaitan, Daniel Razsekar (Jayapangus Press, 2025)
Over the past decade, tourism development in the Lake Toba region has surged significantly. However, this growth often overlooks local wisdom, ecological sustainability, and the spiritual foundations of the local community. Lake Toba is not merely a natural tourist destination but a living space rich in cultural and religious significance. Its majestic landscape holds great potential as a site for interreligious and intercultural dialogue, and can even be interpreted as a cosmic scripture that resonates with harmony and spiritual openness. This study aims to explore and describe how Lake Toba can be strengthened as a space for interfaith and intercultural dialogue, and to analyze how the HKBP Church, as the majority Christian community in the region, can develop a contextual theology of tourism and religious moderation. A qualitative research method was employed, using a historical-critical and contextual hermeneutical approach to Psalm 19:2–5. This was complemented by in-depth interviews with informants representing subjective readers and interpretive communities. The theoretical framework is based on Stephen Bevans’ contextual theology, particularly his three models: translation, anthropological, and praxis. The findings indicate that: (1) nature, as viewed through the lens of the Psalm, is not merely an aesthetic backdrop but a divine revelation that invites spiritual encounter; and (2) spiritual tourism can serve as a means of social transformation, creating space for religious tolerance and moderation that strengthens social cohesion. In conclusion, religion should play an active role in tourism development, particularly by: (1) establishing nature-based liturgical programs and ecological spiritual education within the church; and (2) positioning itself as a cultural and environmental steward by promoting sustainable spiritual tourism in which spirituality, nature conservation, and respect for local traditions are harmoniously integrated.